The Effectiveness of Bioentrepreneurship Learning Using Comics on the Sub Concepts of Angiosperms for High School Students - Yuliana Putri; Ria Yulia Gloria; Asep Mulyani (Scientiae Educatia: Jurnal Pendidikan Sains, 2018)
Biointerpreneurship learning by using comics is one of the contextual learning and can train students' creativity and cognitive abilities. Therefore this study aims to determine the effectiveness of bioentrepreneurship learning using comics, by studying student creativity, students' cognitive abilities, and student responses. This research is a quantitative study with a quasi-experimental method of nonequivalent pretest-posttest control group design. The instruments used for data collection include observation sheets, pre-test post-test, and student response questionnaires. The results showed that the creativity of the experimental class students was better than the control class, the cognitive abilities of the experimental class students improved better than the control class, and the responses of students in the experimental class were included in the strong criteria. Based on the results of the study it can be concluded that learning bioenterprenership using comics effectively increase student creativity, students' cognitive abilities, and positive response from students